Natural course of gastroesophageal reflux disease during infancy - six-month follow-up - Eka Laksmi Hidayati; Agus Firmansyah; Alan R. Tumbelaka (Paediatrica Indonesiana, 2007)
Background Very few data have been published about the naturalcourse of gastro-esophageal reflux (GER) symptoms duringinfancy; further, no risk factors of GER disease (GERD) have beenidentified.Objectives To determine the prevalence and natural course ofregurgitation in infancy and factors of gastroesophageal refluxdisease.Methods A cohort of 223 healthy infants who attended IntegratedHealth Services run by local housewife (Posyandu) of Ciputat –suburb of Jakarta – between March and November 2005.Information on subjects’ history of regurgitation and other reflux-related symptoms was obtained by interviewing mother and diaryrecord. Subjects were followed up to age of 1 year irrespective ofthe clinical status.Results At 6 months of age most infants (56.5%) had regurgitation1 to 3 days per week and only 2.7% infants regurgitated daily.Regurgitation 1 to 3 episodes per day was found in 92.8% ofsubjects. The proportion of infants regurgitation decreasedgradually with age; the proportion for the consecutive 6 to 11month was 100%, 65.5%, 33.6%, 14.3%, 3.6% and 1.3%,respectively. At the age of 1 year no infants was found to beregurgitated. Related symptoms included hiccup (58.3%),vomiting (23.3%) and back arching (2.2%). Feeding problemoccurred in 34.1% infants and occurred more likely in infantswho regurgitate daily compared to 4 – 6 day per week (OR 3.5;95%CI 2.2;5.6) and 1 – 3 day per week (OR 1.8; 95%CI 0.6;0.9).Conclusions Regurgitation in infancy disappears spontaneouslywith age. Reflux-related symptoms are hiccup, vomiting and backarching. Feeding problem occurs most likely in infants whoregurgitate daily.